Admissibility in Criminal Prosecutions of Proof of Other Offenses as Substantive Evidence - Morgan, Clinton J. (1950)
The general rule has been well established that on prosecution for a particular crime evidence which in any manner shows or tends to show that the accused has committed another crime wholly independent of that for which he is on trial, even though it be a crime of the same character, is irrelevant and inadmissible. This statement by the Tennessee court announces the basic rule regarding the matter of proof of other crimes as substantive evidence--a rule which is quoted and adhered to in virtually every American jurisdiction. The evidence is not excluded because it has no probative value, but because its probative value is far outweighed by its prejudicial effect. The fact that a person has committed another crime clearly, under many circumstances, makes it more probable that he has committed the crime charged, but it is equally obvious that the natural and inevitable tendency of the judge and jury would be to give excessive weight to the accused's criminal record. The jurors would very naturally believe that a person is guilty of the crime charged if it is proved to their satisfaction that he has committed a similar offense, or any offense of an equally serious character. To guard against this evil the courts have unanimously adopted the general rule of exclusion stated above.. To this general rule, however, there are many equally well settled exceptions. In fact, the scope of these exceptions is so broad as to have prompted the remark that it is difficult to determine which is the more extensive, the doctrine or the acknowledged exceptions. It is the purpose of this Note to consider these exceptions individually, with emphasis upon the law of Tennessee in this regard